2023
DOI: 10.3390/ijms242316977
|View full text |Cite
|
Sign up to set email alerts
|

Natural Functional Beverages as an Approach to Manage Diabetes

Filomena Carvalho,
Radhia Aitfella Lahlou,
Paula Pires
et al.

Abstract: Diabetes mellitus is a chronic disease, commonly associated with unhealthy habits and obesity, and it is becoming a serious health issue worldwide. As a result, new approaches to treat diabetes are required, and a movement towards more natural approaches is emerging. Consuming fruit and vegetables is advised to prevent diabetes since they contain several bioactive compounds. A simple and effective strategy to include them in the diets of diabetic and obese people is through beverages. This review aims to repor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 145 publications
0
1
0
Order By: Relevance
“…It has been demonstrated that a range of medicinal plants and fruit-and vegetablebased foods can intervene at critical stages of glucose metabolism and could potentially be used to develop new anti-diabetic medications [9,10]. There are multiple mechanisms underlying their anti-diabetic effects, including intervening with the insulin receptor signaling pathways, the translocation of GLUT4 receptors, the activation of PPAR-γ, or the reduction of intestinal glucose absorption [11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that a range of medicinal plants and fruit-and vegetablebased foods can intervene at critical stages of glucose metabolism and could potentially be used to develop new anti-diabetic medications [9,10]. There are multiple mechanisms underlying their anti-diabetic effects, including intervening with the insulin receptor signaling pathways, the translocation of GLUT4 receptors, the activation of PPAR-γ, or the reduction of intestinal glucose absorption [11].…”
Section: Introductionmentioning
confidence: 99%